Flowering behaviour, yield dynamics and fruit quality of Indian gooseberry (Emblica officinalis) in eastern tropical region of India - KUNDAN KISHORE; DEEPA SAMANT; H S SINGH; P SRINIVAS (The Indian Journal of Agricultural Sciences, 2016)
Performance of aonla (Emblica Officinalis Gaerten.) varieties was evaluated with respect to their flowering behaviour, yield and fruit quality at Central Horticultural Experiment Station (ICAR-IIHR), Bhubaneswar during 2011-14. Flower initiated in November and continued till February with the perceptibly long flowering duration (51-85 days). December-January was considered as a critical period for bloom. Post-fertilization fruit dormancy was relatively short (45 days) and fruits took about six months to get matured. Aonla genotypes showed low alternate bearing index (ABI) by exhibiting minimal temporal variation in yield. NA 7 exhibited maximum flowering intensity (82.5%), number of productive branchlets (80.93) and pistillate flowers/branchlet (6.15). It was the most promising variety in eastern tropics due to high yield (42.34 kg/tree), yield efficiency (0.86 kg/m3) and crop density (6.37 fruits/ cm2), whereas, Krishna was found to the second most productive variety in the region. It was observed that fruit yield was not significantly related with flowering intensity, number of productive branchlets and sex ratio. NA 7 had maximum TSS (10.38 Â°B), whereas NA-10 had maximum vitamin C content (365.67 mg/100g). In comparison to subtropical regions, aonla genotypes had low TSS and vitamin C content.